Effect of Iodine (Iodine Polyvinylpyrrolidone complex) on Brucella strains - ΣΕΪΜΕΝΗΣ, Α.; ΣΚΥΡΙΑΝΟΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The possible inhibitory effect of iodine polyvinylpyrrolidone complex (Betadine solution 10%) on the growth of Brucella melitensis Rev.I strain and Br. abortus S. 19 strain, was tested. Dilutions of the product up to 1:10.000 were mixed, in equal volumes, with suspensions of the above strains and inoculated to tryptose-agar medium in petri dishes after lapses of contact time ranging from 30" up to 30'. Following 7 days in 37°C was proved that the growth of Rev. I. strain was completely inhibited even by the highest dilution. The growth of S. 19 in the dilutions 1:6400 and 1:10000 of the product, required 30' of contact before to be minimised